The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1126/sciadv.abd7605
|View full text |Cite
|
Sign up to set email alerts
|

Sperm microRNAs confer depression susceptibility to offspring

Abstract: Evidence that offspring traits can be shaped by parental life experiences in an epigenetically inherited manner paves a way for understanding the etiology of depression. Here, we show that F1 offspring born to F0 males of depression-like model are susceptible to depression-like symptoms at the molecular, neuronal, and behavioral levels. Sperm small RNAs, and microRNAs (miRNAs) in particular, exhibit distinct expression profiles in F0 males of depression-like model and recapitulate paternal depressive-like phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 66 publications
0
95
0
Order By: Relevance
“…Increasing evidence indicates that paternal environmental inputs can affect the metabolic phenotype of the next generation through remodeling of the epigenetic blueprint of sperm. Recently, zygotic injection of total RNAs from isolated sperm or a subset of sperm small non-coding RNAs (sncRNAs) provided direct causal evidence for a role of a ‘sperm RNA code’ for the intergenerational transmission of paternally acquired phenotypes 1 9 . Sperm show dynamic changes in the composition of sncRNAs during the transition from the caput epididymis to the cauda epididymis, where sncRNAs are acquired via epididymosomes 4 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that paternal environmental inputs can affect the metabolic phenotype of the next generation through remodeling of the epigenetic blueprint of sperm. Recently, zygotic injection of total RNAs from isolated sperm or a subset of sperm small non-coding RNAs (sncRNAs) provided direct causal evidence for a role of a ‘sperm RNA code’ for the intergenerational transmission of paternally acquired phenotypes 1 9 . Sperm show dynamic changes in the composition of sncRNAs during the transition from the caput epididymis to the cauda epididymis, where sncRNAs are acquired via epididymosomes 4 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These changes in expression and the phenotypic abnormalities observed in offspring were associated with altered histone methylation levels at genes in sperm (Siklenka et al, 2015). Another epigenetic mechanism that may transmit paternal life experiences to the future father, enhancing his risk for depression are microRNAs, as shown in a recent animal model study (Wang, Chen et al, 2021).…”
Section: The Epigenome Hypothesismentioning
confidence: 89%
“…There is accumulating evidence indicating a significant miRNA contribution to depression, anxiety, and antidepressant action (28,29). A recent preclinical study showed that upregulated miRNA in the sperm of patients with depression significantly inhibited the expression of key genes in the pathway (30). In another study, miRNA-26a-3p was reported to be a putative modulator of antidepressant response (31).…”
Section: Discussionmentioning
confidence: 99%